Measurment of earnini Quality in Commercial Banking - عواد, سعد سلمان (Journal of Economics and Administrative Sciences, 2011)
The importance of earnings quality begin increase in recent year . Particulary after collapse the big companies in U.S.A When the Stock Prices of this Companies negative impact after reporting of transitory & unrealized earnings in the iterim reports , in the same time took to this earnings as absis of Future Predictions .Many of acadmic researchers discusses empirical measures that used to assessments of earnings quality from the perspective of decision usefulness that represent core of FASB's conceptual Framework , and to the economic – based definition of earnings , developed by (Hicks) in 1939.Tise research attempt to test som of earnings quality measures in commercial banks of Iraq through three approaches : Financial ratios , Accrual approach , and Statistices approach . The rescarch Find important diversity in the results of three approaches . However the overall results assert to exist an high quality in earning of commercial banks of Iraq .